Odzyskiwanie pamięci i rehabilitacja ofiar reżimów w ustawodastwie polskim i hiszpańskim - Dobkiewicz, Magdalena (Studia Europaea Gnesnensia, 2012)
The article addresses the efforts of Spaniards and Poles to give a shape to collective memory associated with the period of dictatorships. One of the upshots of these actions is the Spanish memory bill (Ley de Memoria Histórica) and two Polish acts which invalidate verdicts passed against persons persecuted for being involved in the struggle for independent existence of the Polish State and the Act on veterans and persons who fell victim to wartime and post-war repressions. From the text of the Spanish bill one might infer that it does away with Spain of one predominating official memory which eulogized Franco, and replaces it with another one – a memory which is an elegy to Franco’s victims. In Poland, the bills draw on the tradition of independence movements, so as to convince the populace of the will to make amends and to render justice to the aggrieved.